Beautiful Lemons: Adverse Selection in Durable-Goods Markets with Sorting - Peterson, Jonathan R.; Schneider, Henry S. (Management Science, 2017)
We document a basic characteristic of adverse selection in secondhand markets for durable goods: goods with higher observed quality may have more adverse selection and hence lower unobserved quality. We provide a simple theoretical model to demonstrate this result, which is a consequence of the interaction of sorting between drivers over observed quality and adverse selection over unobserved quality. We then offer empirical support using data on secondhand prices and repair rates of used cars from the Consumer Expenditure Survey, and discuss a number of implications for everyday advertising and consumer questions. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2016.2495 . This paper was accepted by J. Miguel Villas-Boas, marketing.